Social Problems and Innovative Solutions: Social Entrepreneurship in Brasov County, Romania - Gotea, Mihaela (Springer Nature Switzerland, 2023)
In a complex world there are various conditions for the generation of a vast palette of social problems, which alter the quality of life for individuals, communities and society. For these problems, the solutions are designed by decisional factors (international, national or local ones) or they are emerging in a bottom-up manner (created by actors in civil society), or a combination of them. This paper aims to explore the linkage between social problems, social innovation and social entrepreneurship, with focus on Romanian context. Social entrepreneurship is a way to find new solutions to complex social problems and a generator of sustainable development of the communities and society at large. Aspects related to the macro-social framework of the social economy in Romania are highlighted. Then, the focus is on a local community, in order to describe some of its challenges and investigate mechanisms to solve these social problems. Using case studies, the paper draws on the experiences of entrepreneurs or intrapreneurs who have succeeded in developing or growing social enterprises. The exploration of their experience intends to clarify what works, and can be seen as a model of good practice.
Keywords: Social Problems; Social Innovation; Social Entrepreneurship; Social Enterprises